Making flexibility more i-deal: advancing work-life equality collectively - Kossek, Ellen E.; Kelliher, Clare (SAGE, 2022)
Current research on negotiated individualized flexible work arrangements focuses on highly paid, skilled professional workers. We refer to this as “flexibility through privilege,” the ability to obtain “flexibility I-deals,” due to high labor market power. Yet as work-life tensions grow across occupations globally, most individuals need increased access to flexibility. As the COVID-19 pandemic illuminated, work-life equality, the ability of workers to have equal access to, opportunity to use, and benefit from flexible working arrangements is a rising form of job inequality. We examine how existing flexibility i-deals can be reconceptualized more broadly to include collectively bargained arrangements across many occupations, and flexible working forms. Our essay advances understanding by (1) broadening notions of the typical employee and occupation involved; (2) expanding negotiation processes beyond an organizational sphere of control; (3) identifying new forms of negotiated flexibility such as control over work-life boundaries and technological availability; and (4) addressing not only employer-employee mutual benefits, but larger societal interests concurrent with new tensions and unintended consequences of mainstreamed implementation. We propose the term “collective flexibility” as the collective right of workers to customize their work schedule, place, workload, boundaries, connectivity, and employment mode with their employer and other stakeholders to benefit employers, employees, and society. We offer a future research agenda. Expanding how we frame and study what a flexibility i-deal is with a collective approach regarding how they are accessed, negotiated, maintained, and who they serve may enhance their potential as a lever for social change to advance economic, social, and health employment rights.
Keywords: flexible work arrangements; i-deals; work-life flexibility; flexibility policies; telework; work-life boundary control; hybrid working